2022
DOI: 10.1155/2022/5242437
|View full text |Cite
|
Sign up to set email alerts
|

NCOA4: An Immunomodulation-Related Prognostic Biomarker in Colon Adenocarcinoma and Pan-Cancer

Abstract: Treatment of cancer in humans requires a thorough understanding of the multiple pathways by which it develops. Recent studies suggest that nuclear receptor coactivator 4 (NCOA4) may be a predictive biomarker for renal cancer. In the present work, TCGA, GEPIA, and several bioinformatics approaches were used to analyze the NCOA4 expression patterns, prognostic relevance, and association between NCOA4 and clinicopathological features and immune cell infiltration. We investigated NCOA4 expression in malignancies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The relationship between NCOA4 mutations and ovarian cancer has not yet been thoroughly investigated. Previous study has reported endometrial cancer populations harboring NCOA4 mutations are associated with a more favorable prognosis compared to wild-type 28 . We also observed higher germline deleterious MMR gene mutations in our study, indicating that lynch syndrome may be more frequently associated with ovarian cancer patients of Southwest China.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between NCOA4 mutations and ovarian cancer has not yet been thoroughly investigated. Previous study has reported endometrial cancer populations harboring NCOA4 mutations are associated with a more favorable prognosis compared to wild-type 28 . We also observed higher germline deleterious MMR gene mutations in our study, indicating that lynch syndrome may be more frequently associated with ovarian cancer patients of Southwest China.…”
Section: Discussionmentioning
confidence: 94%
“…CCL4 demonstrates complex in vivo effects, playing a vital role in immune responses to infection and inflammation. It can activate acute neutrophil inflammation and stimulate the synthesis and release of inflammatory cytokines such as IL-1, IL-6, and TNF-α by fibroblasts and macrophages [ 48 ]. Therefore, the influence of CCL4 on the vulnerability and progression of atherosclerosis may be linked to its role in activating macrophages and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This conundrum underlines the need to comprehensively understand the pathways that lead to the development of tumours [ 27 ]. Therefore, it is necessary to identify additional targets and biomarkers that could be used in the diagnosis and treatment of cancer [ 28 ]. In the field of precision medicine, discovering reliable cancer biomarkers and investigating their function in disease progression could aid in the development of cancer treatments.…”
Section: Discussionmentioning
confidence: 99%